The Role of Stakeholders in the Co-Creation Process in Tourism Village - Fedrina, Rezka; Darmawan, Rahmat (KnE Social Sciences, 2024)
The potential of the tourist village destinations is immense, and it is the responsibility of all stakeholders to ensure that more attention is paid to them. This is especially the case for the Cisaat tourist village, which has a great deal of potential, and the agricultural villages which are the main tourist attractions. As a result, the Co-creation Strategy has become an essential bridge for the management and development of the tourism village in Cisaat. This study seeks to investigate the role of facilitators in the development of tourist villages through a qualitative methodology. Through interviews with representative stakeholders, data was collected. The results of the study reveal that the primary stakeholders in the development of tourism villages are local organizations, communities, industries, universities, and local governments. The outcome of the study is a strategy for the development of tourism products, access to destinations, and the improvement of services for tourists. Keywords: co-creation, stakeholder, tourism village